2018
DOI: 10.1108/maj-05-2017-1558
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of stakeholders’ view of internal audit effectiveness

Abstract: Purpose The purpose of this study is to determine the differences in perception of the key stakeholders on the drivers of internal audit effectiveness, namely, senior management and the audit committee, in relation to identified measures. To be seen as an effective internal audit function, value needs to be added for both these stakeholders. It is thus important for internal auditing to obtain an understanding of what these stakeholders respectively perceive as the most prominent drivers of internal audit effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 28 publications
1
62
0
5
Order By: Relevance
“…Erasmus and Coetzee 2018;Roussy and Brivot 2016). In doing so, we enrich the literature on the IA of risk culture that focused on either the contextual viewpoints of implementers (Carretta et al 2017;Cornia et al 2016;Palermo et al 2016) or the regulatory viewpoints (Power 1999;Ring et al 2016) by highlighting its manifold notion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Erasmus and Coetzee 2018;Roussy and Brivot 2016). In doing so, we enrich the literature on the IA of risk culture that focused on either the contextual viewpoints of implementers (Carretta et al 2017;Cornia et al 2016;Palermo et al 2016) or the regulatory viewpoints (Power 1999;Ring et al 2016) by highlighting its manifold notion.…”
Section: Resultsmentioning
confidence: 99%
“…The third approach explains IA by studying involvement and expectations of different stakeholders (Erasmus and Coetzee 2018;Roussy and Brivot 2016). Studying differing expectations of the major stakeholders and their influence on IA becomes essential considering the influence of a variety of stakeholders on IA practices (Arena and Jeppesen 2009;Covaleski et al 2003), as repeatedly shown through its historical development (Hayne and Free 2014;Parker and Johnson 2017;Spira and Page 2003).…”
Section: Ia Expansions To New Domainsmentioning
confidence: 99%
See 3 more Smart Citations